NK-A 17E-233I: a novel competitive inhibitor of human dihydroorotate dehydrogenase (DHODH) for cancer therapy - Anwar, Mohammed Moustapha ; 0000-0001-5035-8463; Meseguer, Salvador; García-Rodríguez, Néstor; Krupinska, Ewa; Sele, Céleste; Rodríguez-Jiménez, Aida; Verma, Suraj; Sagadevan, Samna; Ramon, Javier; Martí, Ramon; Occhipinti, Annalisa; Angione, Claudio; et al. (Journal of Experimental & Clinical Cancer Research, 2025)
Human dihydroorotate dehydrogenase (DHODH) is the rate-limiting enzyme in pyrimidine de novo synthesis and represents a promising target for cancer therapy. However, current inhibitors of DHODH have limited clinical effectiveness and adverse effects. Herein, we report NK-A 17E-233I, a novel small-molecule inhibitor of the human DHODH enzyme, identified through a prospective virtual screening methodology. Molecular docking and biochemical assays show NK-A 17E-233I functions as a pure or partial competitive inhibitor with respect to the natural substrate, dihydroorotate (DHO). It adopts a distinct binding mode from classical inhibitors that target the flavin mononucleotide (FMN) binding cavity of the hydrophobic tunnel. NK-A 17E-233I exhibits selective cytotoxicity in both human cancer cell lines and patient-derived intestinal organoids, inducing DNA damage, S-phase arrest, and cell death. Unlike Brequinar, NK-A 17E-233I preserves mitochondrial respiration via complexes I and II and maintains ATP-linked basal respiration, avoiding the impairment of the electron transport chain (ETC). Our findings imply the aptitude of NK-A 17E-233I as a novel competitive inhibitor of human DHODH, representing a significant advancement in this field since the 1990s.